CHARACTERISTICS OF LYMPHOCYTE SUBPOPULATION COMPOSITION IN CANCER PATIENTS UNDERGOING COMBINED MODALITY TREATMENT INCLUDING ADAPTIVE IMMUNOTHERAPY - E. V. Abakushina; Yu. V. Marizina; G. S. Neprina; D. V. Kudryavtsev; I. A. Pasova; N. V. Selivanova (Сибирский онкологический журнал, 2016)
Currently, cellular immunity can be estimated using the cluster of differentiation antigens or CD-markers. The panel of CD-markers including 6-8 parameters is usually used for assessment of cellular immunity. In our study we assessed not only subpopulations of T-, B-, NK-, NKT-lymphocytes, but also expression of activation markers (HLA-DR, CD25, CD38, CD69, CD314) using flow cytometry. The increase in the relative and absolute numbers of Treg-lymphocytes and NK-cells as well as the alpha chain of the IL-2 receptor on CD25 lymphocytes was observed in 20 patients with disseminated gastric and colorectal cancer. The percentage of CD25+ -cells and Treg-lymphocytes was also incresaed in 30 patients with skin melanoma. By comparing the expression of lymphocyte activation markers in the two groups of patients, it was shown that patients with gastric and colorectal cancer had the increased percentage of activated CD314+ , CD69+  NK-cells and patients with skin melanoma had the elevated level of activated CD95+  and CD38+ T-lymphocytes. This panel of markers can be used for monitoring immune response to immunotherapy for cancer.